Promising candidates for extracorporeal cardiopulmonary resuscitation for out-of-hospital cardiac arrest - Yo Sep Shin (Nature Portfolio, 2020)
Abstract Precise criteria for extracorporeal cardiopulmonary resuscitation (ECPR) are still lacking in patients with out-of-hospital cardiac arrest (OHCA). We aimed to investigate whether adopting our hypothesized criteria for ECPR to patients with refractory OHCA could benefit. This before-after study compared 4.5 years after implementation of ECPR for refractory OHCA patients who met our criteria (Jan, 2015 to May, 2019) and 4 years of undergoing conventional CPR (CCPR) prior to ECPR with patients who met the criteria (Jan, 2011 to Jan, 2014) in the emergency department. The primary and secondary outcomes were good neurologic outcome at 6-months and 1-month respectively, defined as 1 or 2 on the Cerebral Performance Category score. A total of 70 patients (40 with CCPR and 30 with ECPR) were included. For a good neurologic status at 6-months and 1-month, patients with ECPR (33.3%, 26.7%) were superior to those with CCPR (5.0%, 5.0%) (all Ps < 0.05). Among patients with ECPR, a group with a good neurologic status showed shorter low-flow time, longer extracorporeal membrane oxygenation duration and hospital stays, and lower epinephrine doses used (all Ps < 0.05). The application of the detailed indication before initiating ECPR appears to increase a good neurologic outcome rate.